The Effect Analysis of E-Commerce In The Global Era To Increase Interest In Entrepreneurship In Dimoro Village - Winarsih; Dwi Ayu Istiqomah; Ida Wahyuningsih (LPPM Universitas An Nuur, 2022)
Background: The development of information technology itself is very helpful for entrepreneurs when running a business or business. The form of information technology that is developing very rapidly today is the sale, purchase, distribution and marketing of goods and services through electronic systems, social media and e-commerce. Ecommerce for an entrepreneur can provide effectiveness and flexibility in production and when sending goods and services quickly for software products so that the costs incurred are more efficient. Purpose: This study aims to understand and apply e-commerce to develop business interest in Dimoro village. Methods: This study used a qualitative method which was carried out through observation and interviews with the object directly, namely the Head of UKM in Dimoro village. This method aims to obtain more complete information and can reach a wider scope regarding the influence of e-commerce in the global era to increase entrepreneurial interest in Dimoro village. Conclusion: From the results of observations and interviews conducted, it can be concluded that in increasing business in Dimoro village it is necessary to have an ecommerce application because e-commerce applications are applications to facilitate the buying and selling process and expand market share. In addition, using the application does not need to have a store because it can be managed in their respective homes so that it is more effective and efficient and saves costs. Suggestion: There are still many limitations in this research and need to be developed again for the next research agenda. The scope of this research is still small and in a less broad scope because it is only driven in one place, so that further research can be developed through the addition of variables and the number of objects to be studied.